Dialog Epistemologi: Seni, Ilmu-ilmu Sosial dan Kemanusiaan, Sains dan Teknologi - Yasraf Amir Pilliang (Jurnal Sosioteknologi, 2006)
The development of science, technology, arts, social and humanity science is characterized by the trends of their getting more interrelated and interdependent among one another in a more intense complex relationship. In such condition, the dynamism of knowledge development is highly determined by the openness of any discipline epistemologically, institutionally, and culturally. At the epistemological extent, there is a tendency of epistemological rift in which the disciplinary demarcation or border no longer exists. In such a climate, the endeavour to build a new group of disciplines, especially in a science and technology-based university, should take into account not only epistemological flexibility but also cultural flexibility by introducing or giving an emphasis on an open, inclusive, and dialectical tradition among the experts in this educational institution. Kata kunci: epistemologi, dialogisme, keserumpunan, holistik.